Optimizing identification and management of COPD patients – reviewing the role of the community pharmacist. (2nd November 2016) - van der Molen, Thys; van Boven, Job F. M.; Maguire, Terence; Goyal, Pankaj; Altman, Pablo
Abstract : The aim of this paper was to propose key steps for community pharmacist integration into a patient care pathway for chronic obstructive pulmonary disease (COPD) management. A literature search was conducted to identify publications focusing on the role of the community pharmacist in identification and management of COPD. The literature search highlighted evidence supporting an important role for pharmacists at each of the four key steps in the patient care pathway for COPD management.Step 1 (primary prevention): pharmacists are ideally placed to provide information on disease awareness and risk prevention campaigns, and to encourage lifestyle interventions, including smoking cessation.Step 2 (early detection/case finding): pharmacists are often the first point of contact between the patient and the healthcare system and can therefore play an important role in the early identification of patients with COPD.Step 3 (management and ongoing support): pharmacists can assist patients by providing advice and education on dosage, inhaler technique, treatment expectations and the importance of adherence, and by supporting self‐management, including recognition and treatment of COPD exacerbations.Step 4 (review and follow‐up): pharmacists can play an important role in monitoring adherence and ongoing inhaler technique in patients with COPD. In summary, pharmacists are ideally positioned to play a vital role in all key stages of an integrated COPD patient care pathway from early disease detection to the support of management plans, including advice and counselling regarding medications, inhaler technique and treatment adherence. Areas requiring additional consideration include pharmacist training, increasing awareness of the pharmacist role, administration and reimbursement, and increasing physician–pharmacist collaboration.